2017
DOI: 10.1177/0013161x16687007
|View full text |Cite
|
Sign up to set email alerts
|

The Hiring Process Matters: The Role of Person–Job and Person–Organization Fit in Teacher Satisfaction

Abstract: Purpose: Teachers’ satisfaction with their jobs has reached the lowest point in 25 years. One contributing factor is when teachers experience information-poor hiring processes and do not obtain an accurate preview of their positions, their person–organization (P-O) fit, and person–job (P-J) fit. Sparked by a renewed focus on the variables that can influence teacher satisfaction, the purpose of this study was to examine the relationships among accurate job preview, P-O and P-J fit, and job satisfaction among te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 67 publications
(129 reference statements)
2
44
0
1
Order By: Relevance
“…This showed that EI predicted employee wellbeing because of the partial role of person-job fit. The findings of this study corroborate previous studies where the relationship was found between EI and employee wellbeing (Warr & Inceoglu, 2012;Cifre et al, 2013;Peng & Mao, 2015;Ellis et al, 2017;Chen et al, 2014). EI and perceived person-job fit are employee resources in an organisation that favourably positions them in handling job demands thereby making their health and wellbeing less vulnerable to environmental threat.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This showed that EI predicted employee wellbeing because of the partial role of person-job fit. The findings of this study corroborate previous studies where the relationship was found between EI and employee wellbeing (Warr & Inceoglu, 2012;Cifre et al, 2013;Peng & Mao, 2015;Ellis et al, 2017;Chen et al, 2014). EI and perceived person-job fit are employee resources in an organisation that favourably positions them in handling job demands thereby making their health and wellbeing less vulnerable to environmental threat.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, various positive work outcome construct such as job satisfaction, positive affect, work engagement, burnout has been widely used as indirect indicators of work-related wellbeing (Cifre et al, 2013;Lin et al, 2013); and person-job fit have been found to relate to these indices. Person-job fit is significantly associated with job satisfaction (Warr & Inceoglu, 2012;Cifre et al, 2013;Peng & Mao, 2015;Ellis et al, 2017), work engagement (Cifre et al, 2013;Chen et al, 2014;Enwereuzor et al, 2016). Based on the person-environment fit theory framework and empirical studies support for job-person fit and employee wellbeing relationship, university employees who display higher level of perceived congruence between their personal and job characteristics may be more likely to experience a higher level of work-related wellbeing.…”
Section: Perceived Person-job Fit and Employee Wellbeingmentioning
confidence: 99%
“…Ellis, Skidmore and Combs (2017) provide the salutary warning that after recruitment, high rates of teacher satisfaction are commensurate with those who know what the role involved from the outset or as Bronfenbrenner (2005) describes, the 'person and context'. Ellis et al (2017) add another dimension by replacing the word 'context' with 'job' or 'organisation', thus allowing the teacher to make career decisions based on their knowledge of themselves and their knowledge of the job and organisation. This person -job/organisation fit could be potentially mismatched if there is lack of information provided by the employer.…”
Section: Implication 1: 'Good Recruitment Is Not Just About Appointinmentioning
confidence: 99%
“…This includes understanding how different contexts have encouraged individuals to develop an interest in undertaking this complex role. Using the lens of Bronfenbrenner's ecological systems theory (1979,2005), the purpose of this article has been to explore why people choose to undertake the role of the SENCo -the person in the person context fit (Bronfenbrenner, 2005) or the person in the person -job/organisation fit (Ellis et al, 2017). This research suggests that teachers draw upon a wide range of different reasons when they embark on this career trajectory often through a 'pick and mix' approach drawing on a bricolage of personal, school and wider cultural and policy factors.…”
Section: Implication 1: 'Good Recruitment Is Not Just About Appointinmentioning
confidence: 99%
See 1 more Smart Citation